Tuberculosis related knowledge among the high school students in a selected area of Bangladesh - Karim, Farzana (International Journal of Human and Health Sciences (IJHHS), 2018)
Tuberculosis (TB) is one of the major global public health challenge. In some countries, it is a re-emerging infectious disease. This descriptive type of cross sectional study was carried out among the 200 high school students in a selected semi urban area under Dhaka division of Bangladesh to evaluate their tuberculosis related knowledge. Data were collected by face to face interview of the respondents and analyzed by using SPSS version 16. In this study 53% respondents were male and others were female. Mean age of the respondents was 13.5 years. Among the respondents all of them heard the term tuberculosis. About 36% respondents told that they obtained some information about tuberculosis from television, 29% told book, 17.5 % told radio, 12.5% told newspaper. Majority of the respondents told that tuberculosis is a serious disease whereas 7% told that it is not very serious disease. Majority of the respondents told that cough lasts more than three weeks is the symptom of tuberculosis. More than half of the respondents told that tuberculosis can be transmitted by infected person to person. Among the respondents only 42% told that tuberculosis must be treated by medicine prescribed by doctor. Others (40.5%) said that it is cured by herbal or homeopathy treatment. About 12.5% respondents told that tuberculosis is non curable and 05% told that no treatment is required for this type of disease. About 40% respondents told that they do not know how to prevent tuberculosis disease, 22.5% told that avoidance of TB patients can prevent TB infection. From this study findings it may be concluded that tuberculosis related knowledge among the respondents was not adequate. International Journal of Human and Health Sciences Vol. 02 No. 04 October’18. Page : 220-223